Hepatoprotective Effect of Ginger Induced Experimentally by Dimethoate And Liver Injury in Adult Male Rabbits - Fayrouz Khaled; Ali Shoaib; Mansour Attia (AlQalam Journal of Medical and Applied Sciences, 2020)
Background: Dimethoate (DM) is a widely used organophosphate insecticide and acaridae. Ginger extracts have shown a wide array of beneficial role in the regulation of regular liver functions and the treatment of liver hepatotoxicity. This study was carried out to investigate the possible anti-oxidant activity of ginger extract on the DM-induced effect on liver injury of adult mail rabbits. Methods: Twenty male New Zealand White rabbits were randomly divided into four groups: (1): control group; (2): rabbits were treated with ginger alone (3): rabbits were treated with DM and (4): rabbits were given DM and ginger. Blood, and liver mushed were using for estimation of liver functions in serum and liver. Results: There were statistically significant elevations in the levels of serum alkaline phosphatase (ALP), alanine transaminase (ALT) and aspartate aminotransferase (AST) activities in plasma and liver as affected by treatment with ginger, DM and/or their combination. Treatment with DM resulted in significant increase in the activities of plasma AST, ALT and ALP and caused significant decrease in the activities of these enzymes in liver. Ginger alone caused significant decrease in the activities of AST, ALT and ALP in plasma and insignificant increase in liver. Conclusion: The presence of ginger with DM caused significant decrease in the induction of AST, ALT, and ALP activities in plasma, and insignificant improvement in liver enzymes.